Genetic risk factors for schizophrenia associate with sleep spindle activity in healthy adolescents. (29th August 2018) - Merikanto, Ilona; Utge, Siddheshwar; Lahti, Jari; Kuula, Liisa; Makkonen, Tommi; Lahti‐Pulkkinen, Marius; Heinonen, Kati; Räikkönen, Katri; Andersson, Sture; Strandberg, Timo; Pesonen, Anu‐Katriina
Abstract: Schizophrenia has been associated with disturbed sleep, even before the onset of the disorder, and also in non‐schizophrenic first‐order relatives. This may point to an underlying genetic influence. Here we examine whether weighted polygenic risk scores (PRS) for schizophrenia are associated with sleep spindle activity in healthy adolescents. Our sample comes from a community‐based cohort of 157 non‐schizophrenic adolescents (57% girls) having both genetic data and an overnight sleep EEG measurement available. Based on a recent genome‐wide association study, we calculated PRS for schizophrenia across the whole genome. We also calculated PRS for the CACNA1l gene region, which has been associated with both schizophrenia and sleep spindle formation. We performed an overnight sleep EEG at the homes of the participants. Stage two sleep spindles were detected using an automated algorithm. Sleep spindle amplitude, duration, intensity and density were measured separately for central and frontal derivations and for fast (13–16 Hz) and slow (10–13 Hz) spindles. PRS for schizophrenia was associated with higher fast spindle amplitude ( p  = 0.04), density ( p  = 0.006) and intensity ( p  = 0.04) at the central derivation, and PRS in the CACNA1l region associated with higher slow spindle amplitude ( p  = 0.01), duration ( p  = 0.03) and intensity ( p  = 0.002) at the central derivation. A positive association between genetic variants for schizophrenia and sleep spindle activity among healthy adolescents supports a view that sleep spindles and schizophrenia share similar genetic pathways. This study suggests that altered sleep spindle activity might serve as an endophenotype of schizophrenia.